Decoding dengue’s neurological assault: insights from single-cell CNS analysis in an immunocompromised mouse model - Minyue Qiu; Lixin Zhao; Xiaojia Li; Yipei Fan; Minchi Liu; Dong Hua; Yunkai Zhu; Yinyin Liang; Yu Zhang; Wen Xiao; Xiaofeng Xu; Jintao Li (Journal of Neuroinflammation)
Abstract Background Dengue encephalitis, a severe neurological complication of dengue virus infection, is increasingly recognized for its rising incidence and significant public health burden. Despite its growing prevalence, the underlying mechanisms and effective therapeutic strategies remain poorly understood. Methods Cellular atlas of dengue encephalitis was determined by single-nucleus RNA sequencing. Viral load of dengue virus and the level of cytokines expression was detected by RT-qPCR. The target cells of dengue virus were verified by immunofluorescence. The cytotoxic effect of CD8+ T cell was determined by flow cytometry, immunofluorescence, in vivo CD8+ T cell depletion, adoptive transfer and CCK-8-based cell viability assay. Axonal and synaptic reduction induced by dengue virus infection was demonstrated by RT-qPCR, Western blot, transmission electron microscope and immunofluorescence. Finally, motor and sensory functions of mice were detected by open field test and hot plate test, respectively. Results In this study, we utilized single-nucleus RNA sequencing on brain tissues from a dengue-infected murine model to construct a comprehensive cellular atlas of dengue encephalitis. Our findings identify neurons, particularly inhibitory GABAergic subtypes, as the primary targets of dengue virus. Additionally, immune cell infiltration was observed, contributing to significant neurological damage. Comprehensive analyses of cell-cell communication, combined with CD8+ T cell depletion and transfer restoration experiments, have elucidated the critical role of CD8+ T cells in triggering encephalitis through their interaction with neurons. These cells infiltrate the brain from peripheral circulation, interact with neurons, and induce damage of synapse and axon, accompanied by neurological dysfunction. Conclusion We defined cellular atlas of dengue encephalitis in mouse model and identified the primary target neuron of dengue virus. In addition, we demonstrated the significant cytotoxic effect of CD8+ T cell, which leads to apoptosis of neuron and neurological dysfunction of mice. Our study provides a molecular and cellular framework for understanding dengue encephalitis through advanced sequencing technologies. The insights gained serve as a foundation for future investigations into its pathogenesis and the development of targeted therapeutic approaches.